People's Republic of China : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2019)
-- China has undertaken a number of initiatives since 2002 that have contributed positively to its understanding of ML/TF risk, although some important gaps remain. Its framework for domestic AML/CFT cooperation and coordination is well established. -- China's decentralized financial intelligence unit (FIU) arrangement consisting of China Anti-Money Laundering Monitoring and Analysis Center (CAMLMAC), Anti-Money Laundering Bureau (AMLB), and 36 People's Bank of China (PBC) provincial branches has high potential to produce financial intelligence that supports the operational needs of competent authorities, but its current functioning results in incomplete access by all parts of the FIU to all data, fragmented analysis and disseminations, and limits the development of a holistic view. Therefore, major improvements are needed.